Influence of surface morphology on electrophysical properties of PbTe: Sb films - Saliy, Ya.P.; Nykyruy, L.I. (Physics and Chemistry of Solid State, 2021)
The electrophysical properties of polycrystalline doped semiconductor thin films PbTe: Sb deposited on mica and sital (glass based ceramic) substrates are considered. The thickness dependencies of carrier mobility, of Hall coefficient and of Seebeck coefficient, and the correlations between these parameters for films deposited on different substrate materials were studied. The peculiarities of growth of thin films and their structural parameters are analyzed taking into account the features of the ‘substrate – film’ boundary section.